Two large squirrels (Rodentia, Mammalia) from the Junggar Basin of northwestern China demonstrate early radiation among squirrels and suggest forested paleoenvironment in the late Eocene of Central Asia - Li, Qiang; Ni, Xijun; Stidham, Thomas A.; Qin, Chao; Gong, Hao; Zhang, Limin (Frontiers in Earth Science, 2023)
Fossil evidence is indispensable for studying the derivation, divergence, and dispersal of squirrels as they responded to global Cenozoic climatic and paleoenvironmental change. Among these fossil records, the earliest known definitive fossil squirrels in Eurasia after the Eocene/Oligocene Boundary, slightly younger than the oldest records in North America. Here, we report the discovery of two new extinct large squirrel species from the late Eocene of the Junggar Basin in northwestern China. The dental morphologies of these new taxa represent tree and flying morphotypes, and their estimated body masses are approximately 1.2 kg and 2.6 kg, respectively. In addition, these extinct lineages push the age of the first appearance of Sciuridae in northern Asia into the late Eocene. Together with Douglassciurus and Oligospermophilus from North America, these two new squirrels from the Junngar Basin are the earliest records of sciurids, and analysis of their teeth clearly demonstrates that the three principle morphotypes of sciurids (flying, ground, and tree squirrels) had diverged from one another by the late Eocene. That proposed late Eocene divergence among the major groupings of sciurids is consistent with some molecular clock analyses and helps to document that macroevolutionary timing and pattern. Comparison with modern squirrel analogues for body masses over 1 kg points to these early Chinese species as having occupied forested habitats, and that hypothesis is congruent with published palynological studies. Furthermore, these two new squirrel taxa from Jeminay provide new data to evaluate the examination of the long term aridification of central Asia.